ANALISIS TINGKAT EFISIENSI DAN EFEKTIVITAS REALISASI ANGGARAN BIAYA PROYEK (Media Riset Akuntansi, 2022)
This study contains the results of efficiency and effectiveness analysis of budget realization if “Smart Banking” project cost in 2015-2016 on Bank “X” to the high inconsistency between expenditure budget to the process and its realization. The data used are data from the ongoing project in the period of 2015. The results show that there is inefficient budget and time.